Kristen dan Kenaifan Politik: Kritik atas Sikap Politik PGPI dalam Pilpres 2014 - Victor Silaen (Reformed Center for Religion and Society, 2015)
ABSTRACT:Â Politics is an aspect and a system that is very important in the lives of citizens. All citizens including Christians cannot shy away from politics, because of politics produce various public policies. Thus Christians are supposed to take part in political life, not only in the electoral arena, but also in other areas. In the event the election, churches should not be nae. Churches must wisely give political enlightenment to their congregations, instead of the other way, lead the congregation to elect candidates of certain leaders. Thus the